IDENTIFIKASI TITIK KEPUTUSAN DALAM PROSES BISNIS OTOBUS - Ela Ilmatul Hidayah; Aaziza Mun; Muhammad Ainul Yaqin (Program Studi Ilmu Komputer FMIPA-UHO, 2024)
This study aims to analyze and optimize business processes in bus companies using the ERP (Enterprise Resource Planning) system approach. By employing Business Process Modeling and Notation (BPMN) to map workflows and data-driven analysis to evaluate operational efficiency and customer satisfaction, the study identifies seven key decision points: ticket order validity, seat availability, bus departure scheduling, route planning, invoice creation, maintenance scheduling, and spare parts fulfillment. The implementation of an ERP system with BPMN provides valuable insights and supports process improvements. The study further recommends the development of a more comprehensive ERP system by integrating advanced data analytics and artificial intelligence (AI) to predict operational needs, such as ticket demand, fleet allocation, and route optimization, enhancing both efficiency and responsiveness in customer service. Ultimately, the study concludes that ERP is a strategic solution to sustain and improve the competitiveness of bus companies in the digital era.